2012 IFIP Wireless Days 2012
DOI: 10.1109/wd.2012.6402817
|View full text |Cite
|
Sign up to set email alerts
|

THINPLE - the new online Sociality is built on top of NFC-based Contacts

Abstract: Abstract-The rapid densification of today's online social networks is progressively draining their early value of mirroring real life sociality. This paper describes THINPLE, a novel mobile computing app aiming at building a protected and trusted online social space where the growth of the sociality of a person is only fuelled by contacts in the physical world. THINPLE exploits each physical contact, through the short radio range of Near Field Communication, NFC, to capture the explicit willingness and trustwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…An application called All-I-Touch [ 181 ] helps users to share a product that they wish to buy with their social network by touching the tag that is placed on the product package. In another interesting study [ 182 ], the authors propose an application that aims to create a trusted social network, in which a user builds its own online social space through physical contacts. Users touch their smartphones with another person’s smartphone to initiate a relationship or friendship on a social network.…”
Section: Nfc Applications In Service Domainsmentioning
confidence: 99%
“…An application called All-I-Touch [ 181 ] helps users to share a product that they wish to buy with their social network by touching the tag that is placed on the product package. In another interesting study [ 182 ], the authors propose an application that aims to create a trusted social network, in which a user builds its own online social space through physical contacts. Users touch their smartphones with another person’s smartphone to initiate a relationship or friendship on a social network.…”
Section: Nfc Applications In Service Domainsmentioning
confidence: 99%
“…For example, [41] have developed an application programming interface (API) based on the Neo4j GDBMS to enable functionalities needed with graph databases. Similarly, [17] have used Neo4j to develop a social graph database prototype called THINPLE. THINPLE is built as protected and trusted online social space where the growth of the sociality of a person is only fuelled by contacts in the physical world.…”
Section: Social Graph Approachmentioning
confidence: 99%
“…Pietilainen and Diot also went onto show that devices that spend the most time within these social clusters do not impact on data delivery performance metrics as much as other devices. Moreover, Gaito et al [20] have shown that less than 10% of online friends met during experiments with students. So methods which hope to bootstrap the clustering process using social clusters generated from social networking websites [21] may not provide an improvement to data delivery efficiency in PSNs.…”
Section: Related Workmentioning
confidence: 99%